Gasification characteristics of waste plastics (SRF) in a bubbling fluidized bed: Use of activated carbon and olivine for tar removal and the effect of steam/carbon ratio. (15th April 2022) - Han, Si Woo; Tokmurzin, Diyar; Lee, Jeong Jae; Park, Sung Jin; Ra, Ho Won; Yoon, Sang Jun; Mun, Tae-Young; Yoon, Sung Min; Moon, Ji Hong; Lee, Jae Goo; Kim, Young-Min; Rhee, Young Woo; et al.
Highlights: Activated carbon and olivine are used for tar removal in a bubbling fluidized bed. AC triggers the cracking and reforming of heavier compounds. Olivine is effective for tar removal and H2, CO, CH4 gas increased. Steam gasification significantly increases H2 and CO content. Abstract: This study investigates the gasification characteristics of waste plastic (SRF; solid refuse fuel) and tar removal properties of activated carbon (AC) and olivine using 1 kg/h lab scale bubbling fluidized bed gasifier. The steam gasification was conducted at steam/carbon (S/C) ratio from 1.0 to 2.0 to increase the product gas quality. AC bed gas velocity is 0.12 m/s and temperature is varied from 600 to 800 °C. AC triggers the cracking and reforming of heavier compounds, reducing the tar content by 64% at 800 °C and increases H2 and CO content. Increasing AC bed temperature causes reduction of C2 -C3 hydrocarbons, thus decreasing carbon conversion efficiency (CCE), cold gas efficiency (CGE), and lower heating value (LHV) of product gas. Using olivine as the bed material increases contents of H2, CO, CH4 and reduces content of CO2 in the product gas, therefore improving CCE and CGE. Olivine reduces the tar content up to 32% due to the steam–iron process and increases light aromatics but reduces naphthalene content in tar. Steam gasification significantly increases H2 and CO content of the product gas compared to air gasification. Increasing S/C ratio further increases the H2 and CO content, and the CO2, CH4, and C2 -C3 hydrocarbons decreases due to intensification of water–gas shift, steam reforming, and water–gas reactions. Exceeding S/C ratio above 1.5 decreases the H2 and CO content, but increases CCE, CGE, and LHV of the gas due to higher C2 –C3 hydrocarbons content in the product gas. Increasing S/C ratio above 1.5 also increases condensable tar content of the product gas, increases consumption of AC bed thus reducing its catalytic effect.